Idiopathic pulmonary fibrosis and pulmonary hypertension: Heracles meets the Hydra. (7th April 2020) - Rajagopal, Keshava; Bryant, Andrew J.; Sahay, Sandeep; Wareing, Nancy; Zhou, Yang; Pandit, Lavannya M.; Karmouty‐Quintana, Harry
Abstract : Idiopathic pulmonary fibrosis (IPF) is a fatal lung disease where the additional presence of pulmonary hypertension (PH) reduces survival. In particular, the presence of coexistent pulmonary vascular disease in patients with advanced lung parenchymal disease results in worse outcomes than either diagnosis alone. This is true with respect to the natural histories of these diseases, outcomes with medical therapies, and even outcomes following lung transplantation. Consequently, there is a striking need for improved treatments for PH in the setting of IPF. In this review, we summarize existing therapies from the perspective of molecular mechanisms underlying lung fibrosis and vasoconstriction/vascular remodelling and discuss potential future targets for pharmacotherapy. LINKED ARTICLES: This article is part of a themed issue on Risk factors, comorbidities, and comedications in cardioprotection. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v178.1/issuetoc